Impact of hypertension home-based care on health related quality of life of Nigerian patients: research concept, framework and methodology - Bolarinwa, Oladimeji Akeem; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah; Akande, Tanimola Makanjuola (Community Health Society Malaysia, 2016)
Background: Public health importance of hypertension have been documented all over the world. In recent years, there has been increase cases of hypertension reported in African countries including Nigeria. The current management strategy of hypertensive cases within hospital setting are characterized by high default rate, non-adherence, poor medical outcomes and poor quality of life. While past studies emphasized use of medical outcomes to assess treatment or intervention outcomes, only scanty studies take into cognizance the quality of life that patients live. Because of the chronicity of hypertension, it is important to begin to assess the Health Related Quality of Life (HRQoL) of patients and begin to use such as an impact assessment of treatment or intervention strategies. This study proposed to develop and implement a home based follow-up care (HBFC) intervention and evaluate the impact of the intervention on the HRQoL of hypertensive patients in Nigeria. Materials and methods: This study will be a randomized control trial (un-blinded) to be conducted in 3 stages. Stage 1 will develop HBFC program while in stage 2, patients will be recruited, assessed (baseline data), randomized into 2 arms of study and follow-up for 6 months. The third stage will evaluate the impact of the intervention on HRQoL and disseminate the findings. Data will be collected with the use of structured questionnaire which will contain validated tools like SF-36v2 for HRQoL and Morisky scale for medication adherence. Main outcome measurement will be treatment effect using HRQoL while data would be analyzed using SPSS, version 22. Intention to treat (ITT) analysis concept will be employed and main hypothesis will be tested using paired t-test analysis. Level of significance will be set at p-value of < 0.05 and 95% confidence intervals (CI). Expected outcome: The study will contribute to the existing knowledge on home based care program for hypertensive patients in developing countries where literature is scanty. It will generally give insight into the importance of HRQoL measurement in interventional studies on hypertension and other related chronic diseases in this setting.